The Flipped Classroom: An Overview of its Impact on Economics Learning - Selvita Eka Eviana Purba; Kristiani Kristiani; Khresna Bayu Sangka; Omar Khadeer Hussain (International Journal of Pedagogy and Teacher Education, 2021)
The flipped classroom is a type of blended learning that has been widely applied at various levels of education, from elementary to higher, but there have been few studies on its use in Economics education. The purpose of this article is to provide a brief overview of the impact and effectiveness of the flipped classroom on Economics learning. The research methodology used is a literature study with analysis of several articles about the flipped classroom, which concludes with the research objectives. The study results show that the effects of the flipped classroom can enhance students’ self-reliant and active learning, increase collaboration, and improve learning outcomes. The article provides advice for educators, especially in the field of Economics education, on use of the flipped classroom to maximise student learning. The study conclusion, which compares the flipped classroom learning model in general, shows that the flipped classroom learning model is effective for use in the learning process because students have studied the material before going to class, meaning the teacher no longer dominates the classroom situation and teacher- student interactions become better and more enjoyable.